2020
DOI: 10.1099/ijsem.0.004141
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of Lactobacillus kosoi Chiou et al. 2018 as a later heterotypic synonym of Lactobacillus micheneri McFrederick et al. 2018, elevation of Lactobacillus plantarum subsp. argentoratensis to the species level as Lactobacillus argentoratensis sp. nov., and Lactobacillus zhaodongensis sp. nov., isolated from traditional Chinese pickle and the intestinal tract of a honey bee (Apis mellifera)

Abstract: Lactobacillus kosoi Chiou et al. 2018 and Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 55 publications
0
42
0
Order By: Relevance
“…zhaodongensis, pertaining to Zhaodong County, a county located in Heilongjiang province, PR China, where the bacterium was isolated). Li et al 2020 The description of Lacticaseibacillus zhaodongensis is identical to that proposed for Lactobacillus zhaodongensis [4].…”
Section: Description Of Lacticaseibacillus Zhaodongensis Comb Novmentioning
confidence: 62%
See 3 more Smart Citations
“…zhaodongensis, pertaining to Zhaodong County, a county located in Heilongjiang province, PR China, where the bacterium was isolated). Li et al 2020 The description of Lacticaseibacillus zhaodongensis is identical to that proposed for Lactobacillus zhaodongensis [4].…”
Section: Description Of Lacticaseibacillus Zhaodongensis Comb Novmentioning
confidence: 62%
“…argentoratensis of or pertaining to Argentoratus, the Roman name of the city of Strasbourg in Alsace, France, where the 14 strains were first collected and analysed). Li et al 2020 The description of Lactiplantibacillus argentoratensis is identical to that proposed for Lactobacillus argentoratensis [4].…”
Section: Description Of Lactiplantibacillus Argentoratensis Comb Novmentioning
confidence: 73%
See 2 more Smart Citations
“…are generally members of FLAB, and A. ozensis is, however, an atypical species in the genus due to the presence of a complete adhE gene. Lactobacillus kosoi, isolated from a sugar-vegetable fermented beverage [21], was recently classi ed as a member of the genus Apilactobacillus [10] but was only recently considered a later heterotypic synonym of A. micheneri [22]. Recent study found a strain of Leuconostoc citreum showing FLAB-like poor D-glucose metabolic property, due to the absence of an active promoter region upstream of the adhE gene [14].…”
Section: Discussionmentioning
confidence: 99%